Simplify the product A*B*C*D*E*F
A = (√2)
B = (√(2-√2))
C = (√(2-√(2+√2)))
D = (√(2-√(2+√(2+√2))))
E = (√(2-√(2+√(2+√(2+√2)))))
F = (√(2+√(2+√(2+√(2+√2)))))
(In reply to
Fixing my Problem: by Jer)
The square root symbols don't show up well in the comment.
Apparently only a scholar can edit his own problem once it's already posted. And a scholar can't edit someone else's problem once it's posted.
You could petition the director (bug levik).
Edited on May 16, 2005, 8:46 pm
|
Posted by Charlie
on 2005-05-16 20:43:19 |